Influence of Cyano Substituents on the Electron Density and Catalytic Activity Towards the Oxygen Reduction Reaction for Iron Phthalocyanine. the Case for Fe(Ii) 2,3,9,10,16,17,23,24-Octa(Cyano)Phthalocyanine - Zagal-Moya, J; Zagal-Moya, J; Cardenas-Jiron, G; Aliaga-Vidal, C; Aliaga-Vidal, C; Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Inc., 2020)
Iron(II) 2,3,9,10,16,17,23,24-octa(cyano)phthalocyanine (OCNFePc), was tested as a catalyst for the oxygen reduction reaction (ORR) adsorbed on carbon nanotubes. The composite was analyzed spectroscopically and electrochemically characterized at pH 13 and pH 1. The composite showed close to 4 electron processes at pH 13. Computational analysis indicates that the O2 molecule binds end-on to the metal center and that the dioxygen molecule is dissociated on both the Fe metal center and the corral ring. An Analysis of the molecular electrostatic potential confirms the behavior of cyano residues as electron-withdrawing moieties in OCNFePc. As a result of its catalytic behavior and theoretical analysis of its O2 binding energy, OCNFePc was placed in a high position on a volcano correlation of similar phthalocyanine composites. © 2020 The Authors